EFEKTIFITAS LAUGHING THERAPY DAN RELAKSASI OTOT TERHADAP STRES LANSIA DI PANTI WERDHA MAJAPAHIT - Dessy Ayuningtyas; Julia Ari Santi; Arifatur Rizal; Nurul Mawaddah (MEDICA MAJAPAHIT, 2017)
Â An increase in the number of elderly people in Indonesia causes health problems associated with the elderly. According to Stanley (2006), one of the problems we can see to be a phenomenon in the elderly is stress. Stress gives a total impact of the individual is physical, social, intellectual, psychological and spiritual. One of the stress management that is Laughing Therapy combined with muscle relaxation. This is because the effects caused by stress not only cause psychological changes in the elderly but also on physical changes. The purpose of this study is to determine the effectiveness of the provision of laughing therapy and muscle relaxation as stress management in the elderly. This research uses Quasy Experiment Pretest-Posttest Control Group Design method. Number of respondents were 40 respondents divided into control and treatment groups according to inclusion criteria, Respondents were given laughing therapy and muscle relaxation as much as 6 meetings in 3 weeks. Stress level gauge used is PSS (Percieved Stress Scale). The results of the study were 13 (65%) suffered from moderate stress. In the treatment group, 14 (70%) had mild stress. Analysis of research data using T-Test Paired with pvalue = 0,049 (a <0,05) which means there is giving of laughing therapy and muscle relaxation as stress management at elderly.